Disability among attendees with schizophrenia in a Nigerian hospital: further evidence for integrated rehabilitative treatment designs - Andrew Toyin Olagunju; Dapo Adebowale Adegbaju; Richard Uwakwe (Mental Illness)
Evidence-based rehabilitative treatment is constrained due to limited knowledge about disability and its related factors among individuals with schizophrenia across West Africa. This study aims to investigate the pattern of disability, and the associated factors among individuals with schizophrenia. One hundred consecutively recruited consenting participants were subjected to designed questionnaire to inquire about their demographic and illness-related variables. This was followed by the administration of Structured Clinical Interview for DSM-IV-TR Axis I Disorders and Brief Psychiatric Rating Scale to confirm the diagnosis of schizophrenia and rate severity of symptoms respectively in them. In addition, the World Health Organisation Disability Assessment Scale II (WHODAS-II) was used to assess for disability in all participants. Different degrees of disability based on WHODAS- II mean score of 27.02±3.49 were noted among individuals with schizophrenia, and affectation of domains of disability like self care, getting along with others, life activities and participation in the society among others were observed. In addition, high level of disability was significantly associated with younger adults in the age group 18-44 years (P=0.007), unemployment status (P=0.003), remittance source of income (P=0.034) and ethnicity (P=0.017); conversely, less number of children (P=0.033), less amount spent on treatment (P<0.001) and lower BPRS score (P<0.001) correlated negatively with high level of disability. In spite of clinical stability following treatment, individuals with schizophrenia were disabled to varied degrees, and socioeconomic as well as illness-related factors constituted important correlates. Integration of rehabilitation along with social intervention into treatment design to reduce disability is implied, and further research is also warranted.